(untitled) (Progressive Agriculture, 2019)
Shrimp farming of Bangladesh is one of the most important contributors for its economic development and rural employment generation. The study examined the value chain actors, functions, governance and value chain mapping; estimated value addition in terms of cost and margin in Chalna, Tildanga and Bajua villages of Dacope upazila under Khulna District. Twenty five farmers and 55 traders were interviewed for collecting primary data. Descriptive analysis was performed for reaching the objectives.The study found that farmer, faria, bepari, aratdar, depot owner, commission agent/supplier, processing plant and retailer were value chain actors for shrimp. It was observed that value chain governance was dominated by external parties (legislative governance) and national bodies dominate judicial government. It was identified that processing plants add highest value at Tk. 228 per kg. On the basis of share of profit and cost it was revealed that processing plant was the dominant actor in the chain. Highest value addition, marketing cost and net value addition was Tk. 22800 per quintal, Tk. 13988 per quintal and Tk. 8901 per quintal incurred by processing plant respectively. Percentage of total cost and percentage of total profit was highest for processing plant at 62.85% and 43.71% respectively. The policy implication is that it is necessary to establish storage facility and government monitoring of shrimp markets for the improvement of the present situation. Progressive Agriculture 30 (1): 65-74, 2019